2018
DOI: 10.1007/s40279-018-0917-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Neighbourhood Physical Environmental Attributes and Older Adults’ Leisure-Time Physical Activity: A Systematic Review and Meta-Analysis

Abstract: PROSPERO 2016:CRD42016051180.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
193
6
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(227 citation statements)
references
References 141 publications
22
193
6
6
Order By: Relevance
“…Our results correspond to our previous results with another population shown non-significant relationships between POS accessibility and self-reported leisure time physical activity [27]. In addition, a recent systematic review and meta-analysis in other settings those show a non-significant relationships between POS accessibility and self-reported or objectively-measured leisure-time walking [3]. We found that a novel urban built environment POS, as kilometers of healthy routes promoted by the local government, contained or intersected by a 1 km sausage network walkable buffer was associated with objectively-measured physical activity.…”
Section: Built Environment Weather and Physical Activitysupporting
confidence: 91%
See 2 more Smart Citations
“…Our results correspond to our previous results with another population shown non-significant relationships between POS accessibility and self-reported leisure time physical activity [27]. In addition, a recent systematic review and meta-analysis in other settings those show a non-significant relationships between POS accessibility and self-reported or objectively-measured leisure-time walking [3]. We found that a novel urban built environment POS, as kilometers of healthy routes promoted by the local government, contained or intersected by a 1 km sausage network walkable buffer was associated with objectively-measured physical activity.…”
Section: Built Environment Weather and Physical Activitysupporting
confidence: 91%
“…Although we were unable to differentiate if these healthy routes correlated with others common urban built environment measures commonly used in physical activity and health research, such as residential density, public transport stop access, road intersection density, land use mix or walkability index, we suspect these conditions might strongly affect the local government health policies in the construction of these healthy routes. Moreover, these urban built environment measures show significant relationships between POS accessibility and leisure-time walking [3].…”
Section: Built Environment Weather and Physical Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, no signi cant associations between aesthetics and weekly minutes of recreational walking were observed in the IPEN Adult Latin American countries. This suggests that, in the context of Latin America, aesthetics may promote the adoption of leisure-time PA but may not have a substantial impact on the accumulated amount of leisure-time PA. Interestingly, as in the IPEN Adult study [11], aesthetics were found to be positively related to transportation-PA in the pooled analyses, although this attribute is hypothesized to impact only leisure-time PA [40]. It may be that aesthetically pleasing environments and green spaces can act as motivators for engaging in or spending more time in active transport.…”
Section: Discussionmentioning
confidence: 69%
“…A substantial number of studies have reported significant effects of aspects of the urban environment (residential neighbourhoods, in particular) on physical activity, cardiovascular health and obesity, [14][15][16][17][18] which are established determinants of cognitive health. 8 However, the role of urban environments in relation to brain and cognitive health has received little attention.…”
Section: Introductionmentioning
confidence: 99%